Heart failure with preserved ejection fraction in Asia. (16th August 2018) - Tromp, Jasper; Teng, Tiew‐Hwa; Tay, Wan Ting; Hung, Chung Lieh; Narasimhan, Calambur; Shimizu, Wataru; Park, Sang Weon; Liew, Houng Bang; Ngarmukos, Tachapong; Reyes, Eugene B.; Siswanto, Bambang B.; Yu, Cheuk‐Man; et al.
Abstract : Background: Heart failure with preserved ejection fraction (HFpEF) is a global public health problem. Unfortunately, little is known about HFpEF across Asia. Methods and results: We prospectively studied clinical characteristics, echocardiographic parameters and outcomes in 1204 patients with HFpEF (left ventricular ejection fraction ≥50%) from 11 Asian regions, grouped as Northeast Asia (Hong Kong, Taiwan, China, Japan, Korea, n  = 543), South Asia (India, n  = 252), and Southeast Asia (Malaysia, Thailand, Singapore, Indonesia, Philippines, n  = 409). Mean age was 68 ±12 years (37% were < 65 years) and 50% were women. Seventy per cent of patients had ≥2 co‐morbidities, most commonly hypertension (71%), followed by anaemia (57%), chronic kidney disease (50%), diabetes (45%), coronary artery disease (29%), atrial fibrillation (29%) and obesity (26%). Southeast Asian patients had the highest prevalence of all co‐morbidities except atrial fibrillation, South Asians had the lowest prevalence of all co‐morbidities except anaemia and obesity, and Northeast Asians had more atrial fibrillation. Left ventricular hypertrophy and concentric remodelling were most prominent among Southeast and South Asians, respectively ( P  < 0.001). Overall, 12.1% of patients died or were hospitalized for heart failure within 1 year. Southeast Asians were at higher risk for adverse outcomes, independent of co‐morbidity burden and cardiac geometry. Conclusion: These first prospective multinational data from Asia show that HFpEF affects relatively young patients with a high burden of co‐morbidities. Regional differences in types of co‐morbidities, cardiac remodelling and outcomes of HFpEF across Asia have important implications for public health measures and global HFpEF trial design.